Our Impact 2017-2018 Program Focus Team Report - Hadley, Gregg (My University, 2019)
K-State Research and Extension's program report for 2017-2018. This report to a variety of stakeholders illustrates the statewide extension work for the programming year.
Keywords: Administrative and Research Reports